China in Regional Trade Agreements : Labor Mobility Provisions - World Bank (World Bank, 2012)
This report is structured in three volumes: competition provisions; environment provisions; and labor mobility provisions. The main messages of this three volumes are as follows: 1) competition laws and policies are increasingly being established at the regional level, as they could be instrumental in supporting the benefits of trade and investment liberalization; 2) China may want to use the opportunity of these negotiations to: (a) further discipline its state-owned enterprises;(b) carefully consider the possible role of antidumping policies; and (c) promote and lock-in domestic reforms aimed at improving its domestic competition policies; 3) with a shift of the development agenda from primarily pursuing growth to achieving a more balanced and sustainable development and taking into account China's high reliance on trade, it may be increasingly in China's interest to pro-actively engage its partners on environmental issues in its regional trade agreement (RTA) negotiations; and 4) while the world economy stands to gain massively from liberalization in the mobility of labor, adverse popular reaction to the economic and social impacts of immigrants has kept progress in enhancing global labor mobility well below progress in trade and capital liberalization.